Field Station Weather Reports - M. Knapp; E. A. Adee (Kansas Agricultural Experiment Station Research Reports, 2020)
This report includes the annual summary of precipitation from 2019 at the research locations represented in the 2020 field report and further details about the Kansas River Valley locations and the east central Kansas locations.
Keywords: East Central Kansas; Kansas State experiment field; Kansas River Valley; Kansas State Experiment Field; 2019 growing season weather; Kansas weather